The Optimization of Polymer and Plasticizer Composition in the Formulation of Edible Film Strips Ethanol Extract of Seroja Roots (Nelumbo nucifera Gaerth) as Antioxidant - Rika Sebtiana Kristantri; Tris Harni Pebriani; Ungsari Rizki Eka Purwanto; Orvala Wilakeyne Dhoffaluthfica (Jurnal Kesehatan dr. Soebandi, 2024)
Skin aging can occur if endogenous antioxidants are not sufficient to ward off radical compounds and external antioxidant intake is needed. One plant that contains antioxidants is lotus root (Nelumbo nucifera Gaertn.) and has the potential to be developed into nutraceutical products, namely edible film strips. This research aims to develop edible film strips from ethanol extract of lotus roots as anti-aging by optimizing polymer and plasticizer components, namely HPMC and sorbitol using the Simplex Lattice Design method from Design Expert 13.0 software. The antioxidant activity of the preparation was tested using the 1,1-diphenyl-2-picrylhydrazyl method. Phytochemical screening results showed that the extract contained polyphenols, tannins, flavonoids and saponins. The predicted optimal formula for edible lotus root extract has a HPMC-Sorbitol composition ratio of 2:10 with a desirability value of 0.737. Observation results show that the optimum formula preparation has a thickness of 0.32 mm; pH 3.22; drying shrinkage 6.91%; absorption capacity 49.73%; and disintegration time 31.56 seconds. This value is not significantly different from the physical characteristic value predicted by the software (Sig. 2-tailed > 0.05). The potential anti-aging activity which is identical to the antioxidant activity of the optimum formula is shown by obtaining an IC50 value of 58.6174 ppm which is included in the strong antioxidant group. This is thought to be attributed to the presence of tannin and flavonoid polyphenol compounds in the lotus root extract, where these compounds have hydroxy groups which have been proven to be able to capture free radicals.